Growth and Production of Corn (Zea mays L.) and Spinach (Amaranthus tricolor L.) In Intercropping Pattern Supplemented With Coffe Skin Compost Fertilizer - Yakup, Yakup; Purnama Ria, Rofiqoh; Risna, Rusdan (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
The efforts to improve land use efficiency to increase food crop production can be done with an intercropping system. Intercropping can be done with a food crop and horticultural crop planting system, such as corn and spinach. The purpose of this study was to determine the effect of coffee skin compost on the growth and production of corn and spinach in an intercropping system. The research method used a Randomized Block Design (RBD). The treatment factor were the dose of coffee skin composts consisting of 5 treatments, each treatment repeated 3 times. The treatments used were P0: (Control without treatment) P1: 4 tons/ha of coffee skin compost (2.5 kg/plot) P2: 4.6 tons/ha of coffee skin compost (3 kg/plot) P3: 5.2 tons/ha of coffee skin compost (3.5 kg/plot) P4: 6 tons/ha of coffee skin compost (4 kg/plot). Based on the research results, it was known that intercropping of corn and spinach with the application of coffee skin compost did not have a significant effect on the growth and yield of corn plants. While in spinach plants, the application of coffe skin compost had a significant influence on growth parameters, namely plant height, leaf length and width per week. However, other variables, such as the number of leaf and spinach harvest did not show significant efect. This showed that coffee skin compost tends to affect spinach growth more than corn in the intercropping system. Although the effect on corn was not statistically significant, the highest mean values ​​were observed at P3 (5.2 tons/ha) and P4 (6 tons/ha) treatments in corn and spinach intercropping.